2021
DOI: 10.1002/wrna.1679
|View full text |Cite
|
Sign up to set email alerts
|

Compositional biases in RNA viruses: Causes, consequences and applications

Abstract: If each of the four nucleotides were represented equally in the genomes of viruses and the hosts they infect, each base would occur at a frequency of 25%. However, this is not observed in nature. Similarly, the order of nucleotides is not random (e.g., in the human genome, guanine follows cytosine at a frequency of ~0.0125, or a quarter the number of times predicted by random representation). Codon usage and codon order are also nonrandom. Furthermore, nucleotide and codon biases vary between species. Such bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 187 publications
(235 reference statements)
0
20
0
Order By: Relevance
“…Finally, future studies could investigate whether altering the nucleotide composition of herpes viruses through synonymous mutations could be an effective platform for the generation of rational herpesvirus vaccine candidates or vectors. Modifying codon usage bias through the introduction of synonymous mutations could allow tuneable alterations to expression levels of viral target genes and levels of attenuation, as well as increasing the visibility of viruses to the host’s immune response while maintaining the natural antigenic profile of the virus [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, future studies could investigate whether altering the nucleotide composition of herpes viruses through synonymous mutations could be an effective platform for the generation of rational herpesvirus vaccine candidates or vectors. Modifying codon usage bias through the introduction of synonymous mutations could allow tuneable alterations to expression levels of viral target genes and levels of attenuation, as well as increasing the visibility of viruses to the host’s immune response while maintaining the natural antigenic profile of the virus [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated significant suppression of CpG and UpA/TpA dinucleotide frequencies in the coding regions of RNA and small DNA viruses, which mimics suppression in mammalian genomes [ 12 ]. Artificially increasing dinucleotide frequencies results in a substantial attenuation of virus replication, suggesting dinucleotide bias facilitates recognition of non-self RNA and that viruses have evolved to counter this [ 2 , 16 , 17 , 18 ]. Recently, the antiviral protein ZAP (also known as PARP13), expressed from the ZC3HAV1 gene, was identified as the host factor responsible for sensing CpG dinucleotides in viral RNA [ 19 ].…”
Section: Nucleotide and Dinucleotide Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past decade, many groups have investigated the impact of synonymously increasing the CpG content in the genomes of RNA viruses. Without exception, these studies have determined that genomic CpG 2 enrichment causes viral replication deficiencies (reviewed in (4)). To explain this, it was hypothesised that a cellular antiviral sensor may detect CpG motifs in viral RNAs (5), and in 2017 this idea was confirmed through identification of the cellular protein ZAP (zinc-finger antiviral protein) as a selective binder of CpG motifs in viral RNA transcripts (6).…”
Section: Introductionmentioning
confidence: 99%